2009
DOI: 10.1111/j.1532-950x.2009.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Ovariectomy in Dogs: Comparison Between Single Portal and Two‐Portal Access

Abstract: LapOVE can be performed using single portal access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
170
0
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(181 citation statements)
references
References 35 publications
9
170
0
2
Order By: Relevance
“…Reproductive tract was easily visualized using such technique, due to the pneumoperitoneum, Trendelenburg positioning and amplification of the image using the video system. Single portal techniques for ovariectomy have also been reported as feasible and safe in others domestic species, specially in dogs (DUPRÉ et al, 2009;MANASSERO et al, 2012) and cats (KIM et al, 2011;COISMAN et al, 2014). A 3-port laparoscopic assisted ovariohysterectomy technique using pretied loop ligature was assessed in the canine specie, which resulted in bleeding in three dogs (MAYHEW & BROWN, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive tract was easily visualized using such technique, due to the pneumoperitoneum, Trendelenburg positioning and amplification of the image using the video system. Single portal techniques for ovariectomy have also been reported as feasible and safe in others domestic species, specially in dogs (DUPRÉ et al, 2009;MANASSERO et al, 2012) and cats (KIM et al, 2011;COISMAN et al, 2014). A 3-port laparoscopic assisted ovariohysterectomy technique using pretied loop ligature was assessed in the canine specie, which resulted in bleeding in three dogs (MAYHEW & BROWN, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…6 In addition, in human and veterinary surgery, there has been interest in reducing the number and size of portals in endosurgery, in an attempt to reduce postoperative pain. 1,2,7 In a comparative study in dogs undergoing laparoscopic ovariectomy, the use of 2 cannulae significantly lower the postoperative pain score when compared with the use of 1 cannula or 3 cannulae. 1 However, the same study showed that reducing the number of portals might prolong surgical time.…”
Section: Introductionmentioning
confidence: 98%
“…Minor complications were similar in both groups. 2 Novel computer-controlled bipolar electrocoagulation devices, such as the Ligasure Atlas (Covidien, Massachusetts), facilitate sealing and dividing ovarian pedicles, reduce operative time, and are widely used for surgical procedures in people and animals. [8][9][10][11] A recent study with Vietnamese Pot-bellied pigs demonstrated that open ovariectomy using the Ligasure is a faster surgical technique with less perioperative complications when compared with the ovariectomy with traditional ligatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic procedures are minimally invasive surgical techniques that allow excellent observation, minimal incision, lower complication rates, rapid postoperative recovery, lower pain scores and improved patient convalescence compared with open surgical procedures (Davidson et al 2004;Babkine and Desrochers 2005;Hendrickson 2008;Jimenez Pelaez et al 2008;Dupre et al 2009). We are not aware of any previously reported method for laparoscopic abomasal cannulation in sheep.…”
mentioning
confidence: 99%